Frantz Fanon and the #MustFall Movements in South Africa - Luescher, Thierry M (International Higher Education, 2016)
What started in early 2015 as a series of protests at the University of Cape Town against the statue of Cecil John Rhodes expanded by the end of the year into a nationwide student movement under the label #FeesMustFall. This article analyzes the development and characteristics of the movement as a networked student movement along with its ideological inspiration in the work of Frantz Fanon.